Tsetse elimination : its interest and feasibility in the historical sleepin sickness focus of Loos Islands, Guinea - (:unkn) unknown (My University, 2009)
Guinea is the West African country which is currently the most prevalent for sleeping sickness. The littoral area is the region where most of the recent sleeping sickness cases have been described, especially the mangrove sleeping sickness foci of Dubreka and Boffa where Glossina palpalis gambiensis is the vector. Loos islands constitute a small archipelago 5 km apart from the capital, Conakry. Medical, animal, and entomological surveys were implemented in these islands in Oct-Nov 2006. No pathogenic trypanosomes were found in these surveys. The locally very high tsetse densities (up to more than 100 tsetse/trap/day) linked to pig rearing, constitute a high potential risk for humans (taking into account populations movements with neighboring active sleeping sickness foci of the Guinea littoral, and the history of sleeping sickness on these islands), and for the economically important pig rearing, as well as a danger for tourism. This situation, associated to the possibility of elimination of these tsetse populations due to low possibility of reinvasion, led the National Control Program to launch a tsetse elimination project following an “area wide” strategy for the first time in West Africa, which participates in the global objective of the PATTEC (Pan African Tsetse and Trypanosomosis Eradication Campaign).
Keywords: African Research